Accidental hypothermia–an update. Issue 1 (December 2016) - Paal, Peter; Gordon, Les; Strapazzon, Giacomo; Brodmann Maeder, Monika; Putzer, Gabriel; Walpoth, Beat; Wanscher, Michael; Brown, Doug; Holzer, Michael; Broessner, Gregor; Brugger, Hermann
Abstract Background This paper provides an up-to-date review of the management and outcome of accidental hypothermia patients with and without cardiac arrest. Methods The authors reviewed the relevant literature in their specialist field. Summaries were merged, discussed and approved to produce this narrative review. Results The hospital use of minimally-invasive rewarming for non-arrested, otherwise healthy, patients with primary hypothermia and stable vital signs has the potential to substantially decrease morbidity and mortality for these patients. Extracorporeal life support (ECLS) has revolutionised the management of hypothermic cardiac arrest, with survival rates approaching 100 % in some cases. Hypothermic patients with risk factors for imminent cardiac arrest (temperature <28 °C, ventricular arrhythmia, systolic blood pressure <90 mmHg), and those who have already arrested, should be transferred directly to an ECLS-centre. Cardiac arrest patients should receive continuous cardiopulmonary resuscitation (CPR) during transfer. If prolonged transport is required or terrain is difficult, mechanical CPR can be helpful. Delayed or intermittent CPR may be appropriate in hypothermic arrest when continuous CPR is impossible. Modern post-resuscitation care should be implemented following hypothermic arrest. Structured protocols should be in place to optimise pre-hospital triage, transport and treatment as well as in-hospital management, including detailed criteria and protocols for the use of ECLS and post-resuscitation care. Conclusions Based on new evidence, additional clinical experience and clearer management guidelines and documentation, the treatment of accidental hypothermia has been refined. ECLS has substantially improved survival and is the treatment of choice in the patient with unstable circulation or cardiac arrest.